Design, Synthesis, and Structural Study of a Shiff Base Ligand Precursor of Metallosupramolecular Architectures - Paula Domínguez-Carbón; Sandra Fernández-Fariña; Miguel Martínez-Calvo (Chemistry Proceedings, 2024)
The spontaneous association of organic ligands and metal ions has given rise to what is known as metallosupramolecular chemistry. This emerging field of chemistry has gathered significant attention due to the numerous supramolecular structures that can be obtained, which have applications in diverse areas, such as materials chemistry, biomedical chemistry, and catalysis, among others. In this context, Schiff base ligands are among the most commonly used ligands for the synthesis of helicates and mesocates. In this study, the Schiff base ligand H2L was designed, synthesized, and characterized. This ligand is potentially dianionic and tetradentate [N2O2], with a long and semiflexible spacer, making it a bicompartmental ligand that promotes the formation of dinuclear helicate compounds. Additionally, the presence of bulky tert-butyl and ethyl groups at specific positions of the skeleton is crucial for enhancing the formation of such structures instead of mesocates. The synthesis was carried out through an imine condensation reaction between two equivalents of 4-(tert-butyl)-2-hydroxybenzaldehyde and one equivalent of 4,4′-methylenebis(2,6-diethylamine) in the presence of p-toluenesulfonic acid monohydrate as a catalyst. The ligand was characterized using standard techniques, and suitable crystals were obtained for study using X-ray diffraction.